School bullying - Smith,Peter K. (2013)
Bullying is defined as a systematic abuse of power; the development of the research program on school bullying is outlined over four phases. The distinctive nature of cyberbullying, and also of identity-based bullying, is outlined. Measurement methods are discussed, and the kinds of prevalence rates obtained. A range of risk factors for involvement as a bully, or victim, are summarized. A range of school-based interventions are described, together with discussion of a meta-analysis of their outcomes. In summary, research and practice have gone hand-in-hand in the research reviewed, and have had some success in at least reducing what is a significant problem in the lives of many children.